STUDI KUALITAS HASIL PENGOLAHAN AIR LIMBAH - KASUS SALAH SATU HOTEL BERBINTANG DI BALI - Sudipa, N.; Mahendra, M.S.; Sudana, I.B. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Water is well thought-out as one of the basic need of human life. Beside its significant role in incomecontribution in the region, tourism industry is almost blamed as an environmental demolisher and polluter inBali. This matter writer interest for research something result quality waste water processing at one casehotel and specific as know bacteriology and chemistry quality, because the result of quality hotel waste waterprocessing very influential about water of river already polluted as physical, chemistry and bacteriology.The study aimed to investigate water quality of Ayung River at the nearest outlet of a star hotel STP and atupper-site rive..The research of methodology is hotel waste water analysis be based on the Minister of EnvironmentLife Regulation number 52, 1995. Analysis result waste water process and water ofr river be based onGovernment Regulation number 82, 2001. The water analysis results evidently showed that water sample taken during the 1st - 3th weeks beforeprocessing at hotel’s STP were classified as heavily polluted based on water quality class I, II, III, and IV,with lowest pollution index (PI) of 33.23 and highest at 42.56. Amazingly, samples taken after STPprocessing were categorized as heavily polluted as well, based on water quality class I II, III, and IV. Thelowest PI was 13.4 and the highest at 22,15. Water sample taken at the nearest STP outlet at river wascategorized as slightly polluted based on water quality class I and fill quality criteria based on water qualityclass II, III, and IV. Water sample taken at upper-site of Ayung River was categorized as slightly pollutedbased on water quality class I, and fill quality criteria polluted based on criteria of water quality class II, III,and IV.
Keywords: Pollution Index, WWTP, Waste, Water Quality, Pollution